2022
DOI: 10.17843/rpmesp.2022.391.9830
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas y epidemiológicas de equinococosis quística en niños de un centro terciario en Perú

Abstract: La equinococosis quística (EQ) en niños es un problema de salud pública. Para describir las características clínicas y epidemiológicas de la EQ se revisaron los registros de 55 niños con diagnóstico confirmado de EQ admitidos entre 2017 y 2019 en un centro quirúrgico referencial del Perú. Se analizaron los datos demográficos, las manifestaciones clínicas y el tratamiento. El 61,8% (34/55) de los niños fue de sexo masculino. La edad promedio fue de 9,25 años (DE: 2,79); un 16,4% tuvo diagnóstico previo de EQ, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…More than half of our study participants were registered as children aged 11-17 years. Huamán et al [47], Salazar-Mesones et al [48], and Talaiezadeh et al [49] found a higher number of cases in the age group 5-9 (90/177, 50.8%), 6-11 (37/55, 67.3%), and the age group 6-10 (46/76, 60.5%), indicating an early exposure to the parasite [48]. Preschoolers and young elementary school children are more susceptible to CE due to poor hygiene standards and close contact with dogs [50].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of our study participants were registered as children aged 11-17 years. Huamán et al [47], Salazar-Mesones et al [48], and Talaiezadeh et al [49] found a higher number of cases in the age group 5-9 (90/177, 50.8%), 6-11 (37/55, 67.3%), and the age group 6-10 (46/76, 60.5%), indicating an early exposure to the parasite [48]. Preschoolers and young elementary school children are more susceptible to CE due to poor hygiene standards and close contact with dogs [50].…”
Section: Discussionmentioning
confidence: 99%